Greening tea consumtion / Maisarah Abd Rahim...[et al.] - Abd Rahim, Maisarah; Abdullah, Noor Azlina; Idris, Mariam; Azmin, Suzani (Universiti Teknologi MARA, Kedah, 2013)
Greening tea consumption would be one of the alternatives that help energizing innovative ecosystem. It is a way to reduce, reuse or recycle a waste thing which refers to reused tea bag and loose leaf tea. Tea bags or even loose leaf tea always can be used more than once, whether for a second cup of tea or by using it for numerous purposes. Rather throw it away to dustbin which is considered as a waste, it is better to reuse or recycle it for certain purposes. Imagines how much can we cut down our waste packaging which refer to individual tea bag whereby we have thrown out about 1095 tea bags each year assuming that we use only once a tea bag per cup and drinks on average three cups of tea per day. Tea bags and loose leaf teas can be multipurpose which they can be reused for cleaning, health and beauty, kitchen purpose, gardening, painting, dye fabrics, tell the future and self- analyze. As a conclusion, greening our tea consumption actually would give many good impact to our daily life which we are not realized on and would save our ecosystem in the future.